New religious immigrants in the Great Plains: a study of mostly white congregations receiving foreign-born pastors - Todd, Jan E. (Kansas State University, 2020)
In 2019 in Kansas and Nebraska, 113 predominately white United Methodist churches were served by 84 foreign-born pastors, an increase of 223% since 2013. This is a new phenomenon in the region as the Great Plains Annual Conference has trained, vetted and deployed foreign-born pastors to mostly white locations at greater rates since 2013. I am interested in the relationships and level of trust that develops between the mostly white community and the foreign-born pastor, indicating their reception. I began my inquiry with the assumption that the immigrant-native relationship develops differently between foreign-born pastors and the mostly white communities as compared to other immigrant-native relationships and/or native and native-born pastor relationships in similar settings. This study was designed to observe, record, analyze and describe a baseline case for the purpose of future comparison to similar appointments in order to build theory that pertains to the explanation of how these relationships develop and their possible effects on society. Grounded in Georg Simmel’s phenomenological theory utilizing “the Stranger” as ideal type and Nicolette-Manglos Weber’s ideas on the role religion plays in the reception and assimilation of migrants, I used a qualitative mixed methods approach, acting as participant observer in both congregations in order to apply theory. Applying the aspects of the merchant/stranger and native community to the foreign-born pastor-mostly white community relationship under the social location of the local church, I gathered data through the tools of observation, artifact collection and in-depth interviews, to look for themes that might indicate what kind of relationships had developed. Finding three connecting themes between the two parties in two different locations, I was able to identify how the overarching values of faith, governance and family aided the development of relationships for some to the level of personal trust. Comparing these three themes, two mechanisms indicating how personal trust developed in this case were identified as multiple mutual discoveries and the development of the foreign-born pastor as a non-threatening global-guide. Keywords: ethnography, immigration, phenomenological theory, religion, trust
Keywords: Religion; Immigration; Foreign-born; Reception; Trust; Simmel